Healing through Photography – A reflection on the Brightening Our Home Fires Project in the remote hamlet of Ulukhaktok, Northwest Territories - Goose, Annie; Badry, Dorothy (First Peoples Child & Family Review, 2013)
This creative piece of work and writing showcases the work of a woman participant from the community of Ulukhaktok in the Northwest Territories (NT). Ulukhaktok is located on Victoria Island above the Arctic Circle. This community shares land with its neighbors in Cambridge Bay, Nunavut; located on the north end of the island. The hamlet of Ulukhaktok, NT and many small, remote and isolated places in the territories reflect a rich cultural Inuit heritage in regions, settlement areas and communities. There is a deep sense of interconnectedness within the North in a vast landscape that is known as home to Inuit culture. The purpose of the Brightening Our Home Fires Project (BOHF) was to work in four communities in the NT on a project related to prevention of Fetal Alcohol Spectrum Disorder in the north. A co-researcher living in the NT suggested the community of Ulukhaktok (formerly known as Holman Island, NT) as a place to visit and invite participation Annie Goose supported this project through participation, acted as a translator and supported us by facilitating meetings within the community. Annie is the primary author of the work shared in this paper. It was my privilege to share in this work and support the knowledge development and exchange that deeply highlights the impact of the Brightening Our Home Fires Project. This work speaks to the possibility of Photovoice in giving voice to unheard experiences in a creative and innovative way on complex areas of health. This article will be of interest to people who are interested in topics such as Northern Canada, qualitative research, women’s perspectives on health and healing, and those interested in Photovoice as a methodology.